Attentional Control According to Ball Location and Its Relation To The Skill of Scoring Accuracy From Set-Pieces In Football - Latif, Ahmed (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Evaluate the self-control according to the ball’s location in the Salahuddin education team for the preparatory stage of football. To identify the relationship between attentional control of ball location and the skill of accuracy of scoring from set-pieces in the Salahuddin education football team. The researcher hypothesised. There is a statistically significant correlation between the attentional control of the ball and the skill of accuracy of scoring from set-pieces in the Salahuddin education team for the preparatory stage of football. The researcher used the descriptive correlation method suitable for the nature of the research and the research community, which consisted of the players of the Salahuddin education team (22). The research sample consisted of 10 players randomly selected (45.40%) from the research population. Conclusions, The research sample shows a positive correlation between attentional control according to the ball’s location and scoring accuracy skill. The research sample scored high in the ability to maintain body balance through the results obtained in the test. The researcher recommended: The researcher recommends paying attention to the skill of scoring accuracy and giving it enough time in the training curricula for coaches. Conduct a similar study by finding a relationship between scoring skill with other qualities, or finding a relationship between attentional control or other saliva. It is recommended that mindfulness training be incorporated into training programmes to improve performance in static football situations.